Dichotomous impact of affinity on the function of T cell engaging bispecific antibodies. Issue 7 (12th July 2021) - Poussin, Mathilde; Sereno, Arlene; Wu, Xiufeng; Huang, Flora; Manro, Jason; Cao, Shanshan; Carpenito, Carmine; Glasebrook, Andrew; Powell Jr, Daniel J; Demarest, Stephen
Abstract : Background: Bispecific T cell engagers represent the majority of bispecific antibodies (BsAbs) entering the clinic to treat metastatic cancer. The ability to apply these agents safely and efficaciously in the clinic, particularly for solid tumors, has been challenging. Many preclinical studies have evaluated parameters related to the activity of T cell engaging BsAbs, but many questions remain. Main body: This study investigates the impact of affinity of T cell engaging BsAbs with regards to potency, efficacy, and induction of immunomodulatory receptors/ligands using HER-2/CD3 BsAbs as a model system. We show that an IgG BsAb can be as efficacious as a smaller BsAb format both in vitro and in vivo. We uncover a dichotomous relationship between tumor-associated antigen (TAA) affinity and CD3 affinity requirements for cells that express high versus low levels of TAA. HER-2 affinity directly correlated with the CD3 engager lysis potency of HER-2/CD3 BsAbs when HER-2 receptor numbers are high ( 200 K/cell), while the CD3 affinity did not impact potency until its binding affinity was extremely low (<600 nM). When HER-2 receptor numbers were lower ( 20 K/cell), both HER-2 and CD3 affinity impacted potency. The high affinity anti-HER-2/low CD3 affinity BsAb also demonstrated lower cytokine induction levels in vivo and a dosing paradigm atypical of extremely high potency T cell engaging BsAbs reaching peak efficacy at doses >3 mg/kg. This data confirms that low CD3 affinity provides an opportunity for improved safety and dosing for T cell engaging BsAbs. T cell redirection also led to upregulation of Programmed cell death 1 (PD-1) and 4-1BB, but not CTLA-4 on T cells, and to Programmed death-ligand 1 (PD-L1) upregulation on HER-2 HI SKOV3 tumor cells, but not on HER-2 LO OVCAR3 tumor cells. Using this information, we combined anti-PD-1 or anti-4-1BB monoclonal antibodies with the HER-2/CD3 BsAb in vivo and demonstrated significantly increased efficacy against HER-2 HI SKOV3 tumors via both combinations. Conclusions: Overall, these studies provide an informational dive into the optimization process of CD3 engaging BsAbs for solid tumors indicating that a reduced affinity for CD3 may enable a better therapeutic index with a greater selectivity for the target tumor and a reduced cytokine release syndrome. These studies also provide an additional argument for combining T cell checkpoint inhibition and co-stimulation to achieve optimal efficacy.Background